Enhanced pressure & proximity sensitivities of a flexible transparent capacitive sensor with PZT nanowires. (February 2019) - Pang, L; Zhao, Q L; Sheng, T Y; He, G P; Di, J J; Su, T T; Tan, P P
Abstract: Capacitive pressure & proximity multi-function sensors are wildly used in applications such as 3D touch screen and electronic skin. However, those sensors could not meet rigorous requirement for accurate quantitative monitoring due to the lower permittivity of the dielectric material. Pb(Zrx Ti1-x )O3 (PZT) material is featured in remarkably high dielectric constant. Here in this work, we present a flexible, transparent capacitive proximity & pressure multi-function sensor with PZT single crystal nanowires (NWs) and polydimethylsiloxane (PDMS) composite as dielectric layer. Experimental results confirmed the perovskite lattice structure. The length of the nanowires is about 50-100 μm, with diameter in magnitude of hundred nanometers. The sensor with PZT NWs could yield excellent pressure sensitivity for nearly 89 MPa −1, which is about 10 times larger than that of the one only with PDMS dielectric layer. The proximity sensing property was also improved with adding PZT NWs in PDMS dielectric layer. Therefore, the performance of our sensor was significantly improved by the utilization of PZT NWs. And such kind of techniques could also be contributed to the development of practical applications like human-machine interface and distance monitoring systems.